Loosening of Access Threshold and Downturns in Listed Firms Performance: A Quasi-Natural Experiment from the “IPO Green Channel” for Poverty Alleviation - Yi Sun; Chunying Cui; Ya Gao; Chunyan Zhao (Discrete Dynamics in Nature and Society)
The China Securities Regulatory Commission (CSRC) proposed the green channel policy for poverty alleviation Initial Public Offerings (IPOs), aiming to help poverty-stricken areas reduce poverty and increase income, but it has an impact on the business performance of the companies involved. This paper uses data from public annual reports of listed companies to construct a policy intervention group and a control group and comparatively analyzes the degree of annual performance downturn of newly listed companies in A-share from 2016 to 2017 through a counterfactual method, and the results show that the “IPO green channel” policy for poverty alleviation has an obvious negative effect on listed enterprises in poverty-stricken counties. The results show that enterprises listed via the green channel have more significant performance downturn than those listed normally during the same period. This paper suggests that the distortion of the market issuance system causes the declining of the quality of IPO firms. Finally, this paper suggests that regulators should cooperate with local governments actively to ensure the smooth implementation of the government’s poverty alleviation efforts while balancing market equity and efficiency. The SFC should take more consideration of institutional compatibility for policy output in financial poverty alleviation to avoid institutional alienation and distortion of corporate behavior.